Analisis Data Seismik Refraksi dengan Metode Generalized-Reciprocal - Ashadi Salim (Bina Nusantara University, 2012)
The analysis of seismic refraction data by the generalized reciprocal method can be used for delineating undulating refractors. The forward and reverse times of arrival at different geophones with XY distance along a refraction profile, are used for calculating time depth. The seismic wave velocity in refractor may be obtained from velocity analysis function, and the depth of refractor under each geophone is obtained from time-depths function. This method has been applied at one line of seismic refraction measurement that was 440 m long with 45 geophone positions. The measurement obtained 20 m as the optimum XY-value and 2250 m/s as the velocity of seismic wave in refractor, and the undulating refractor topography with the depths varies 10.4 – 22.1 m. The optimum XY-value was obtained from approximate calculation derived from the observation, that was indicated the absent of undetected layer.